KERAJAAN MAJAPAHIT: DINAMIKA DALAM SEJARAH NUSANTARA - Deny Yudo Wahyudi (Jurnal Sejarah dan Budaya, 2013)
Abstract. Majapahit is one of Nusantara big kingdoms in influence of Hindhu-Budha age. As big kindom, Majapahit had glorious and sad history dynamic. Many things can be explored from history of Majapahit because it has abundant data sources, both artifact and textual data or news from the other countries. The historical dynamic can be basic of history wisdom in the present time.